Enhancing Interpersonal Intelligence through the Implementation of a Discussion-Based Learning Model in the Aqidah Akhlak for Grade IX Students at Madrasah Tsanawiyah Negeri 2 Jambi - Juliana, Rina; Yuisman, Dedi; Yansah, Alrudi; Khamim, Siti; Mawaddah, Mawaddah; Cahyani, Chairunnisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study investigates the implementation of the Discussion-Based Learning (DBL) model to enhance students’ interpersonal intelligence in the Aqidah Akhlak subject at Madrasah Tsanawiyah Negeri 2 Jambi City. The research was motivated by the low level of engagement and cooperation among Grade IX E students, which highlighted the need for a learning strategy that could optimize social interaction in the classroom. Employing Classroom Action Research (CAR) with the Kemmis and McTaggart model, the study involved three cycles, each consisting of two meetings. Data were collected through observation, interviews, tests, and documentation, and analyzed using both qualitative and quantitative approaches. The results revealed a steady improvement across the three cycles. Teacher activities increased from 73.43% in Cycle I to 87.5% in Cycle II, and 92.96% in Cycle III, while student activities rose from 72.65% to 85.15% and 92.18% respectively. Student test scores also improved, with averages of 73% in Cycle I, 77% in Cycle II, and 86% in Cycle III, meeting the expected success indicators. These findings suggest that the DBL model effectively enhances interpersonal intelligence, with students achieving a “good” category of 86%. In conclusion, the DBL model offers a practical and effective learning strategy to foster interpersonal intelligence, character development, and social skills among Madrasah Tsanawiyah students.